Organizational protection for whistleblowers: a cross-national study. Issue 4 (2nd April 2020) - Chordiya, Rashmi; Sabharwal, Meghna; Relly, Jeannine E.; Berman, Evan M.
ABSTRACT: Whistleblowing is recognized as an effective means to mitigate organizational corruption. However, there is little empirical research that broadens our understanding of organizational strategies that enhance perceived organizational protection for whistleblowers. We aim to fill this gap in the literature by empirically examining a multi-pronged approach to improve this organizational outcome in diverse countries and contexts. A multi-dimensional theoretical framework utilized in this study emphasizes the role of an ethics-oriented climate; ethical leadership behaviours; structural provisions for ethics management, and an awareness of whistleblower protection laws in enhancing perceived organizational protection for whistleblowers.